Synthesis of Some Phenylpyrazolo Benzimidazolo Quinoxaline Derivatives as Potent Antihistaminic Agents - C. H. Sridevi; K. Balaji; A. Naidu; R. Sudhakaran (E-Journal of Chemistry)
2,3-Diphenyl quinoxaline (NI) was fused with benzimidazole (NII) by a methylene bridge, which was then allowed for acetylation. The acetylated product (NIV) was made to react with different aromatic aldehydes to give chalcones (NV1-NV5). Chalcones refluxed with substituted acid hydrazides to afford different phenyl pyrazolo benzimidazole quinoxaline derivatives (NVI 1-NVI 15). The structure of chalcones and phenyl pyrazolo benzimidazole quinoxaline derivatives were confirmed by m.p, TLC and spectral data. All the synthesized compounds were screened for their antihistaminic activity. Compounds NVI-3, NVI-12, NVI-13, NVI-14 and NVI-15 were shown good % protection of antihistamic activity.